It’s about time! Teachers’ perspectives on supportive and hindering contextual conditions for implementing innovations in schools - Mareike Ehlert; Marie Adloff; Elmar Souvignier (Education Inquiry)
Implementation processes are significantly influenced by contextual conditions. To investigate which context factors are implicitly salient for teachers, we conducted interviews with N = 43 elementary school teachers who gave recommendations for designing effective teacher professional development for implementing a reading innovation into their school. On average, teachers mentioned M = 26 contextual factors unprompted to explain their recommendations. Among these, time and material resources as well as factors regarding their colleagues (cooperation, readiness for innovation, prior knowledge) were most frequently mentioned. While most contextual factors were consistently negatively framed (lacking time, staff and financial resources), teachers classified collegial cooperation, their colleagues’ prior knowledge and material resources at their school both as a barrier and as a resource. The analysis of a code map revealed that a lack of time co-occurred most frequently with a lack of personnel resources and insufficient staff prior knowledge. However, time resources also often co-occurred with positive views on collegial cooperation and material resources. These findings suggest that PD programmes should specifically address teachers’ time resources and consider cooperation and prepared material as resources to overcome context constraints.